The Role of Calcitonin in Predicting the Extent of Surgery in Medullary Thyroid Carcinoma: A Nationwide Population-Based Study in Norway. Issue 3 (29th June 2019) - Opsahl, Else Marie; Akslen, Lars Andreas; Schlichting, Ellen; Aas, Turid; Brauckhoff, Katrin; Hagen, Anne Irene; Rosenlund, Alf Frimann; Sigstad, Eva; Grøholt, Krystyna K.; Jørgensen, Lars H.; Bjøro, Trine
Abstract : Background: Preoperative predictors for the need of prophylactic lymph node dissection in the lateral neck have been studied in patients with medullary thyroid carcinoma (MTC). Objectives: To evaluate the ability of serum calcitonin to predict the extent of surgery needed in the lateral neck. Methods: This retrospective population-based cohort study includes data from 94 of 139 patients with MTC surgically treated in Norway from 2003 to 2016. Patients were identified in the 4 regional centers treating MTC and by the Cancer Registry of Norway, and grouped according to calcitonin levels. In 58 patients without distant metastases or disease progression to the next tumor level (NPNL), data were compared in prognostic groups (N0-NPNL), (N1a-NPNL), and (N1b-NPNL). Results: At calcitonin levels ≤500, 501–1, 000, and >1, 000 pmol/L, metastatic lymph nodes in the lateral neck were found in 16, 50, and 71% of the patients, respectively. In the prognostic groups, 19% of N0-NPNL patients had calcitonin >500 pmol/L and 17% of N1b-NPNL patients had calcitonin ≤500 pmol/L. In multivariate analysis, factors predicting biochemical cure and calcitonin level ≤500 pmol/L were no metastatic lymph nodes in the lateral neck ( p = 0.030) and tumor diameter ≤20 mm ( p < 0.001), respectively. Factors related to metastatic lymph nodes in the lateral neck were extrathyroidal extension ( p = 0.007) and no biochemical cure ( p = 0.028). Conclusions: Basal calcitonin cannot predict the need for prophylactic lateral lymph node dissection in patients with MTC. Further prospective, randomized studies are warranted.